ISLAMIC ECONOMIC PRINCIPLES AND PRODUCTION ACTIVITIES THOUGHT OF IMAM AL-GHAZALI FROM HIS BOOK “IHYA’ ULUM AL-DIN” - Try Astuti, An Ras; Hamid Habbe, Abdul; Wahab, Abdul (Dinasti Publisher, 2022)
This article describes the relevance of Imam Al Ghazali's thoughts to the context of the current consumption needs of Islam. The presence of Islam with its beliefs and principles in it, this belief is built on the foundation of God with the consequences of the birth of the principles of Nubuwwah, Khuluqiyyah, Justice, Insaniah, Help and Cooperation. All of these principles in reality affect economic activity, both distribution, production and consumption. Imam AL Ghazali as one of the Islamic economic thinkers participated in providing related ideas about Production in Islam that presents Allah swt in every production activity. On the other hand, according to Imam AL Ghazali, the factors of production include land, labor, technology, production management, technology and raw materials. Furthermore, regarding the classification of production, namely a discussion of the types of production, namely 1) basic industry, textiles for clothing, construction for housing, and state activities, 2) supporting industries (steel industry development, and forest resources), 3) complementary activities related to milling and burning of agricultural products. Finally, regarding the stages of production, Al Ghazali acknowledged that there are stages of production that require division of labor, coordination and cooperation. Regarding its relevance to production activities according to Imam Al Ghazali's view. Many phenomena are related to Imam Al Ghazali's thinking, such as the increase in UMKMs which are factors supporting the success of economic activities including production activities, but some phenomena that are not in line with Imam Al Ghazali's thinking are producers who do not heed the values ??of virtue and justice in their production activities.